INTEGRATED ESTIMATION OF REPRODUCTIVE HEALTH IN SCHOOLGIRLS OF IRKUTSK - O. V. Kravtsova; V. V. Dolgikh; V. P. Ilyin; L. F. Sholohov; L. A. Grebenkina (Acta Biomedica Scientifica)
We studied physical and sexual development of schoolgirls living in Irkutsk. It was shown that somatic pathology plays important role in reproductive health development.